Tribological Properties of Novel Multi-Walled Carbon Nanotubes and Phosphorus Containing Ionic Liquid Hybrids in Grease - Vyavhare, Kimaya; Aswath, Pranesh B. (Frontiers in Mechanical Engineering, 2019)
A continuing quest exists to develop high-performance grease capable of meeting extreme demands of high energy efficiency and durability of modern mechanical systems. In this study, multi-walled carbon nanotubes (MWCNT) and ionic liquids (IL) either singly or as a binary additive system were prepared to study the tribological performance of lithium greases under boundary lubrication condition. The combination of MWCNT and IL can benefit from their respective lubricating mechanism to minimize friction and wear. To test this hypothesis, MWCNT and IL are tested individually and compared with combined MWCNT-IL additive mixture within lithium-based greases. MWCNT-IL gelatinous hybrids were prepared by inducing physical non-covalent interactions between MWCNTs and phosphorous based ILs through ultrasonication and magnetic stirring. Four different phosphorous based ILs, Choline bis(2-ethylhexyl)-phosphate, Choline dibutyl-dithiophosphate, Methyl-tributyl-phosphonium dimethyl-phosphate, Tetra-n-butyl-phosphonium O,O-diethyl-dithiophosphate were used. Four ball tribological test configuration was used to assess wear and friction properties of fabricated greases. The lubrication mechanism of these additives was elucidated through analysis of worn surfaces using surface characterization techniques like SEM, EDS, and stereo optical microscopy. All greases that contain ionic liquid exhibited better tribological performance compared to grease with ZDDP. The maximum reduction of the coefficient of friction (COF) of 60% and wear scar diameter (WSD) reduction of 25% was observed for greases containing MWCNTs and phosphonium cation based ILs hybrids as an additive. Results indicated either worse or comparable anti-wear behavior in greases with MWCNT-IL hybrids as compared to greases that only contained IL or MWCNT. The antagonistic interaction between MWCNT and IL has been postulated to occur when MWCNT adversely interacts with IL formed tribofilms, negating the benefit from IL resulting in increased wear in greases with binary mixtures of MWCNT-IL.